Nucleation and growth of oriented layered hydroxides on polymer resin beads - Du, Y; Hu, G; O'Hare, D (RSC Publishing, 2009)
Two types of layered metal hydroxides (layered Mg/Al double hydroxides and cobalt hydroxides) have been grown on the surface of cation-exchanged polymer resin beads. SEM images of the Mg/Al double hydroxide that nucleated on the surface of the Mg²⁺/Al³⁺ -exchanged resin beads show it to have an initial LDH shell of ca. 150 mn and that this shell is constructed from a monolayer of LDH crystallites aligned edge-on. At longer reaction times LDH particles grow on top of this shell and lie flat on the surface. The overall thickness of the LDH coating is ca. 180 nm and it has been shown to have uniformly grown on the surface of the polymer bead. Layered α and β-type cobalt hydroxide can also be grown on the surface of Co²⁺ -exchange resin beads.